Thermal solar energy storage in Jurassic aquifers in Northeastern Germany: A simulation study. (April 2017) - Kastner, O.; Norden, B.; Klapperer, S.; Park, S.; Urpi, L.; Cacace, M.; Blöcher, G.
Abstract: This contribution studies the usability of aquifer thermal energy storage (ATES) for seasonal solar heat storage by means of thermo-hydraulic modeling. The geological setting refers to the North East German Basin (NEGB), specifically a site approx. 50 km west of Berlin, Germany. The considered storage formation is located in Jurassic sandstones at about 270 m depth below surface, showing an in-situ (undisturbed) formation temperature of around 17 °C and appropriate hydraulic storage properties. The paper considers idealised doublet systems in faulted as well as unfaulted reservoir domains and studies the energy- and mass transport of simulated ATES systems. Five perennial loading/unloading series of solar thermal energy are investigated, assumed to be harvested by a hectare-sized flat plate collector field which is modeled employing climate data of the considered region. The simulation results exemplarily show how the storage system develops temperature-conserving recovery fractions of up to 80% heat recovery during the first years of operation. Highlights: Investigation of aquifer thermal energy storage (ATES) for saisonal solar thermal heat storage. Analysis of the thermo-hydraulic transport characteristics of the solar/ATES system by means of transient subsurface FEM modeling. Geological model refers to an existing site located in the State of Brandenburg, Germany. The site is characteristic of the geology of the farer northeast German Basin. The study bears significance for the sedimentary geology of this region.